Chromium adsorption capacity from tannery wastewater on thermally activated adsorbent derived from kitchen waste biomass - Md. Abul Hashem; Maimona Wadud Mim; Nujhat Noshin; Modinatul Maoya (Cleaner Water)
Environmental sustainability has gained greater acceptance as an approach to achieving the objective of a secure ecosystem with a reliable management system. The best strategy for maintaining a healthy ecosystem is waste management. In this present study, chromium (Cr) adsorption capacity from real tannery wastewater on thermally activated adsorbent, equipped from Cucurbita moschata (pumpkin) peel is described. The adsorbent features were investigated by implementing Fourier transform infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), and pHpzc (point of zero charges) analysis. The Cr adsorption was identified by EDX analysis. SEM images were analyzed to record surface morphological modifications. The adsorbent has a pHpzc of 8.7. The thermally activated adsorbent is used to treat the wastewater, in a batch experiment with varying parameters including contact time, adsorbent dose, and pH. Under optimal circumstances, 50 mL of wastewater was mixed with 2.5 g of adsorbent, agitated for 10 min, allowed to settle, and then the Cr concentration was evaluated. The Cr level in untreated effluent and in filtrate was 3178.6 mg/L, and 12.1 mg/L, respectively. The capability of Cr adsorption and Cr removal efficiency was 3164.46 mg/g and 99.32%, correspondingly, at a pH of 7.2. The biochemical oxygen demand (BOD), chloride (Cl-), and chemical oxygen demand (COD) showed a decreasing percentage of 96.58%, 55.62%, and 95.01%. The Cr adsorption fitting for pumpkin peel adsorbent follows the Pseudo second-order (PSO) kinetic and Freundlich isotherm model. Thus, this investigation established the efficiency of using pumpkin peel as an adsorbent for Cr tanning effluent treatment.